Unexplained complexity of the mitochondrial genome and transcriptome in kinetoplastid flagellates - Lukes, Julius; Hashimi, Hassan; Zíková, Alena (Current genetics, 2005)
Kinetoplastids are flagellated protozoans, whose members include the pathogens Trypanosoma brucei, T. cruzi and Leishmania species, that are considered among the earliest diverging eukaryotes with a mitochondrion. This organelle has become famous because of its many unusual properties, which are unique to the order Kinetoplastida, including an extensive kinetoplast DNA network and U-insertion/deletion type RNA editing of its mitochondrial transcripts. In the last decade, considerable progress has been made in elucidating the complex machinery of RNA editing. Moreover, our understanding of the structure and replication of kinetoplast DNA has also dramatically improved. Much less however, is known, about the developmental regulation of RNA editing, its integration with other RNA maturation processes, stability of mitochondrial mRNAs, or evolution of the editing process itself. Yet the profusion of genomic data recently made available by sequencing consortia, in combination with methods of reverse genetics, hold promise in understanding the complexity of this exciting organelle, knowledge of which may enable us to fight these often medically important protozoans.
Keywords: Animals; Genome, Protozoan; kinetoplastová DNA; Kinetoplastida; RNA Editing; Mitochondria; Transcription, Genetic; Genes, Mitochondrial; RNA protozoální; messenger RNA; RNA, Protozoan; genom protozoální; mitochondrie; RNA, Messenger; genetická transkripce; DNA, Kinetoplast; mitochondriální geny; editace RNA; exprese genu; zvířata; Gene Expression